The phenotypic and genetic features of arrhythmogenic cardiomyopathy in the pediatric population - Kofeynikova, Olga; Alekseeva, Daria; Vershinina, Tatiana; Fetisova, Svetlana; Peregudina, Olga; Kovalchuk, Tatiana; Yakovleva, Elena; Sokolnikova, Polina; Klyushina, Alexandra; Chueva, Kseniia; Kostareva, Anna; Pervunina, Tatiana; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction The present study aimed to describe the phenotypic features and genetic spectrum of arrhythmogenic cardiomyopathy (ACM) presented in childhood and test the validity of different diagnostic approaches using Task Force Criteria 2010 (TFC) and recently proposed Padua criteria. Patients and methods Thirteen patients (mean age at diagnosis 13.6 ± 3.7 years) were enrolled using “definite” or “borderline” diagnostic criteria of ACM according to the TFC 2010 and the Padua criteria in patients <18 years old. Clinical data, including family history, 12-lead electrocardiogram (ECG), signal-averaged ECG, 24-h Holter monitoring, imaging techniques, genetic testing, and other relevant information, were collected. Results All patients were classified into three variants: ACM of right ventricle (ACM-RV; n = 6, 46.1%), biventricular ACM (ACM-BV; n = 3, 23.1%), and ACM of left ventricle (ACM-LV; n = 4, 30.8%). The most common symptoms at presentations were syncope (n = 6; 46.1%) and palpitations (n = 5; 38.5%). All patients had more than 500 premature ventricular contractions per day. Ventricular tachycardia was reported in 10 patients (76.9%), and right ventricular dilatation was registered in 8 patients (61.5%). An implantable cardiac defibrillator was implanted in 61.5% of cases, and three patients with biventricular involvement underwent heart transplantation. Desmosomal mutations were identified in 8 children (53.8%), including four patients with PKP2 variants, two with DSP variants, one with DSG2 variant, and one with JUP. Four patients carried compound heterozygous variants in desmosomal genes associated with left ventricular involvement. Conclusion Arrhythmias and structural heart disease, such as chamber dilatation, should raise suspicion of different ACM phenotypes. Diagnosis of ACM might be difficult in pediatric patients, especially for ACM-LV and ACM-BV forms. Our study confirmed that using “Padua criteria” in combination with genetic testing improves the diagnostic accuracy of ACM in children.